Long-term speech and language deficits and associated neural correlates in survivors of paediatric posterior fossa tumours - Hodgson, Olha (2018)
Background: The present research is the first multi-modal study of language deficits in long-term PFT survivors to date. In addition to a detailed neuropsychological assessment of language, this thesis investigated neural correlates of language processing by employing functional (fMRI) and diffusion (DTI) magnetic resonance imaging techniques. Method: Twenty-one PFT survivors, aged 16-21, and twenty-two matched healthy volunteers completed a series of neuropsychological assessments, task-based language fMRI study (targeting semantic retrieval and speech articulation), and a DTI study. The patients’ clinical profiles and oro-motor functioning were also analysed. Results: Patients demonstrated significantly poorer performance in semantic content, expressive and receptive skills, verbal memory, reading and writing, visuo-motor coordination and non-verbal intelligence, with elevated internal variability of the linguistic profiles, when compared to controls. Semantically-related language skills contributed more to the between-group differences than non-verbal cognitive skills. A significant association between language and non-verbal cognitive abilities in both patients and controls was unconfounded by the age and disease. On fMRI, patients lacked metabolic response in the pre-central and post-central gyri during semantic retrieval. Broca’s, Wernike’s and Geschwind’s areas responded similarly in both hemispheres, with no significant differences between the groups. In all participants Language Content Index predicted the BOLD response on the border of the left lateral occipital cortex and angular gyrus. Expressive Language Index predicted BOLD response in the right frontal pole, paracingulate gyrus, superior frontal gyrus, and middle frontal gyrus. In healthy controls, articulation of speech was associated with activation in the Crus I and Crus II of the right cerebellar hemisphere. Semantic load triggered activation in the Crus VI and VIIb of the vermis, as well as right lobules V and VI of the cerebellum. DTI revealed a global decrease in the fractional anisotropy and increase in the diffusivity scalars in patients, compared to controls, but not different between those patients that received and did not receive radiotherapy. Patients also demonstrated significant reduction in FA index in the bilateral arcuate fasciculus and increased diffusivity in the bilateral SCP. The FA index in the segments of the left-hemispheric cortico-spinal tract, anterior thalamic radiation, superior longitudinal fasciculus and inferior fronto-occipital fasciculus, positively predicted Language Content Index score in patients. Clinical profiles analysis indicated that younger age at diagnosis, radiotherapy treatment and longer duration of mutism (if present) were associated with the poorest language outcomes. Patients with the longest recovery time demonstrated the best manual dexterity abilities. 38% of the patients that met the criteria for a diagnosable language disorder also had reduced oro-motor functioning and reduced FA within left arcuate fasciculus, compared to the remaining patients. Conclusions: Despite the fact that PFTs do not directly impact cortical language-associated areas, patients, particularly those treated with radiotherapy at a younger age, demonstrate deficits in all aspects of language processing. Semantic processing difficulties in PFT survivors are underpinned by the diminished cortical metabolic response during associated task performance, and microstructural changes in the left-hemispheric white matter. Tumours affecting the right cerebellar hemisphere may further predispose patients to developing difficulties in accessing language semantics.